UV-VIS Absorption Spectral Studies of N, N′-Bis(salicylidene)ethylenediamine (Salen) in Different Solvents - Elsherif, Khaled Muftah; Zubi, Ahmed; Shawish, Hana; Almelah, Eman; Abajja, Salima (Iraqi Journal of Science, 2019)
In the present study, the influence of various solvents on UV-VIS absorption spectra of N,N-Bis(salicylidene)ethylenediamine (Salen) has been investigated. Salen ligand has two absorption maxima (around 260 and 320 nm). To explain the obtained spectra, the frequencies and molar absorptivity values were combined with solvent properties using a total solvatochromic equation suggested by the Kamlet and Taft. The multiparametric examination denotes that non-specific dipolar interactions of the solvents (π*) with the solute play a significant role in absorption maxima in pure solvents. The ionization constant (pKa) of salen in methanol has been determined by spectrophotometric measurements. Two graphical methods have been applied to evaluate the ionization constant with resulting average value of 8.61.